Skewness of mean transverse momentum fluctuations in heavy-ion collisions - Giacalone, Giuliano; Gardim, Fernando G.; Noronha-Hostler, Jacquelyn; Ollitrault, Jean-Yves (Physical review, 2021)
We propose the skewness of mean transverse momentum ⟨pt⟩ fluctuations as a fine probe of hydrodynamic behavior in relativistic nuclear collisions. We describe how the skewness of the ⟨pt⟩ distribution can be analyzed experimentally, and we use hydrodynamic simulations to predict its value. We predict, in particular, that ⟨pt⟩ fluctuations have positive skew, which is significantly larger than if particles were emitted independently. We elucidate the origin of this result by deriving generic formulas relating the fluctuations of ⟨pt⟩ to the fluctuations of the early-time thermodynamic quantities. We postulate that the large positive skewness of ⟨pt⟩ fluctuations is a generic prediction of hydrodynamic models.